2011
DOI: 10.1371/journal.pone.0025363
|View full text |Cite
|
Sign up to set email alerts
|

Content-Based VLE Designs Improve Learning Efficiency in Constructivist Statistics Education

Abstract: BackgroundWe introduced a series of computer-supported workshops in our undergraduate statistics courses, in the hope that it would help students to gain a deeper understanding of statistical concepts. This raised questions about the appropriate design of the Virtual Learning Environment (VLE) in which such an approach had to be implemented. Therefore, we investigated two competing software design models for VLEs. In the first system, all learning features were a function of the classical VLE. The second syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Although not tested in this paper, in other research, we have also shown that PR has an important role and that peer feedback increases the chances to perform well at the exam (Wessa et al, 2011). All these findings empirically validate the, often theoretical, assumption of a more constructivist approach, in which peer interactions are indispensable to create mutual knowledge, despite their lack of expert knowledge.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Although not tested in this paper, in other research, we have also shown that PR has an important role and that peer feedback increases the chances to perform well at the exam (Wessa et al, 2011). All these findings empirically validate the, often theoretical, assumption of a more constructivist approach, in which peer interactions are indispensable to create mutual knowledge, despite their lack of expert knowledge.…”
Section: Discussionsupporting
confidence: 80%
“…Even if an e-learning system is used in both ways, there is still an important relationship between the technological design of the system and the efficiency of the learning process (Wessa et al, 2011).…”
Section: Pedagogical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations